Millenial Generation's Perspective On Healing Tourism Post Covid-19 Pandemic In Sumedang Regency - Irena Novarlia (Eduvest - Journal of Universal Studies, 2022)
Study background need will post healing tourism covid-19 pandemic. Destination study is for knowing perspective Generation Millennials about healing tourism, the factors that influence healing tourism, and the efforts made for carry out post- healing tourism covid-19 pandemic. Study this use method study quantitative with analysis descriptive. Research results prove part big from they state not enough know (35%) true meaning from healing tourism but often use term the in everyday especially post covid-19 pandemic. Influencing factors _ perspective generation millennial about the need for post- healing tourism the biggest covid-19 pandemic among them for get rid of boredom or bored during the period of Scalable Social Restrictions Big (34%), and the effort made generation millennial for do post healing tourism the biggest covid-19 pandemic is sports (walking) around village / complex, cycling, and swimming (24%). With so, everything activity related tourism_ with destination could pleasant heart, mind, and cheap rousing is part from healing tourism products and worthy developed as one _ opportunity awaken sector industry tourist post covid-19 pandemic.